2021
DOI: 10.1016/j.ejon.2021.101956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a self-monitoring intervention in breast cancer patients suffering from taste alterations induced by chemotherapy: A randomized, parallel-group controlled trial

Abstract: This study evaluates the effect of a self-monitoring intervention on taste alterations in breast cancer patients undergoing outpatient chemotherapy. Methods: The study was a randomized controlled trial. Thirty-four participants were divided into two groups: a self-monitoring (SMG) group (n = 17) and a control group (CG) (n = 17). A conceptual framework was developed with reference to the components of self-management, cognitive behavioral therapy, and the concepts of self-monitoring. Interventions were based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…It has been demonstrated that the enhanced expression of cytokines in taste buds can cause taste-related disorders and increase programmed cell death of taste cells when interferon (IFN)-α and IFN-γ are activated [ 32 ]. Among the mechanisms of post-CT taste alterations, the following have been proposed: olfactory receptor cells and taste bud damage, peripheral and central neuropathy, such as neuronal cell deterioration and neurotransmission blockage (involving the VII, IX, and X cranial nerves), mucosal injury, xerostomia, concomitant infections/inflammations requiring specific therapies, and psychological effects [ 10 , 20 ]. Establishing the precise mechanisms through which each drug or therapeutic scheme impairs neurosensorial cells is difficult [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that the enhanced expression of cytokines in taste buds can cause taste-related disorders and increase programmed cell death of taste cells when interferon (IFN)-α and IFN-γ are activated [ 32 ]. Among the mechanisms of post-CT taste alterations, the following have been proposed: olfactory receptor cells and taste bud damage, peripheral and central neuropathy, such as neuronal cell deterioration and neurotransmission blockage (involving the VII, IX, and X cranial nerves), mucosal injury, xerostomia, concomitant infections/inflammations requiring specific therapies, and psychological effects [ 10 , 20 ]. Establishing the precise mechanisms through which each drug or therapeutic scheme impairs neurosensorial cells is difficult [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the physical disability of BC patients by worsening body image and future perspective can have a profound negative psychological impact [ 22 , 53 ], often forcing changes in their social and relational habits both at home and outside home [ 23 , 55 ]. Indeed, BC patients are generally women, who may have to prepare meals for their families while coping with their taste alterations [ 10 ]. It has been reported that women with dysgeusia chose not to eat as much, impaired their eating time, and/or lost interest in preparing meals for themselves and/or their family [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study [29,30], we reported that an approach combining self-monitoring with goal-setting and feedback techniques is effective in improving symptoms. This study examines whether self-monitoring interventions that incorporate symptom management recording and observation into daily life are effective in improving self-management skills, mental stability, and quality of life in CIPN patients with low adjuvants.…”
Section: Introductionmentioning
confidence: 99%